Mitral annular plane systolic excursion and tricuspid annular plane systolic excursion for risk stratification of acute pulmonary embolism. Issue 7 (14th June 2020) - Matos, Jason D.; Balachandran, Isabel; Heidinger, Benedikt H.; Mohebali, Donya; Feldman, Stephanie A.; McCormick, Ian; Litmanovich, Diana; Manning, Warren J.; Carroll, Brett J.
Abstract: Introduction: Risk stratification for acute pulmonary embolism (PE) incorporates metrics of right ventricle (RV) function. Significant RV dysfunction influences left ventricular (LV) function, though LV function metrics are not utilized for stratifying outcomes in patients with PE. Mitral annular plane systolic excursion (MAPSE) is a linear echocardiographic (TTE) measure that evaluates longitudinal LV function and may aid in risk stratification for acute PE. Methods: Using a single‐center database of patients with PE from 2007 to 2014, MAPSE was calculated for all TTE's available with sufficient quality (n = 362). A MAPSE of ≥11 mm was used as a normal reference. Thirty‐day adverse outcomes were defined as administration of vasopressor, fibrinolytic therapy, open embolectomy, or 30‐day PE‐related mortality. Odds ratios (OR) and adjusted OR (AOR) were calculated using logistic regression analysis. Tricuspid annular plane systolic excursion (TAPSE) measurements were incorporated to determine the additive benefit of MAPSE. Results: Compared with the reference MAPSE ≥ 11 mm and LVEF > 50%, patients with MAPSE < 11 mm and an LVEF > 50% had worse outcomes (AOR 2.94 [95% CI: 1.08–7.98], P  = 0.035). Among patients with LVEF > 50%, the presence of both a MAPSE < 11 mm and TAPSE < 16 mm was associated with greater odds of adverse outcomes compared with isolated depressed TAPSE (AOR 10.75 [95% CI: 3.06–37.8], P  < 0.01 vs AOR 1.68 [95% CI: 0.18–15.6], P  = 0.65). Conclusion: A depressed MAPSE, in patients with preserved LVEF, is associated with worse outcomes in patients with acute PE. The addition of MAPSE to TAPSE appears to have a greater prognostic value than either alone and may further aid in risk stratification, but for confirmation further prospective data are needed.